2005
DOI: 10.1073/pnas.0506347102
|View full text |Cite
|
Sign up to set email alerts
|

Structure of stochastic dynamics near fixed points

Abstract: We analyze the structure of stochastic dynamics near either a stable or unstable fixed point, where the force can be approximated by linearization. We find that a cost function that determines a Boltzmann-like stationary distribution can always be defined near it. Such a stationary distribution does not need to satisfy the usual detailed balance condition but might have instead a divergence-free probability current. In the linear case, the force can be split into two parts, one of which gives detailed balance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
233
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 156 publications
(235 citation statements)
references
References 24 publications
0
233
0
2
Order By: Relevance
“…Following earlier studies [1,2,19,20], we describe a system capable of undergoing steady-state stochastic circulation as a Brownian particle of mobility µ moving through a static force landscape F(r) at absolute temperature T . Such a description applies naturally to the motion of a colloidal particle in an optical force field, and also may be applied to more general systems such as an ensemble of identical particles interacting through conservative forces and confined by a force landscape.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Following earlier studies [1,2,19,20], we describe a system capable of undergoing steady-state stochastic circulation as a Brownian particle of mobility µ moving through a static force landscape F(r) at absolute temperature T . Such a description applies naturally to the motion of a colloidal particle in an optical force field, and also may be applied to more general systems such as an ensemble of identical particles interacting through conservative forces and confined by a force landscape.…”
Section: Theorymentioning
confidence: 99%
“…Our approach is based on the observation that systems governed by linear forces can be mapped to a generalization of the Ornstein-Uhlenbeck process, for which a general solution is known [19]. For nonlinear forces, a common approach is to solve the system using perturbation theory [20].…”
Section: Theorymentioning
confidence: 99%
“…According to Eqs. (12) and (14), [28] The time evolution of φ(t) is evaluated assuming minor change of V (t) in the phase space, i.e, −π < φ(t + ∆t) − φ(t) ≤ π. The argument is based on that the sampling interval ∆t ∼ 0.5 ms is faster than the autocorrelation time ( few milliseconds ) of V (t).…”
Section: Txmmentioning
confidence: 99%
“…For example, R. Filliger and P. Reimann [11] introduced a Brownian gyrator, in which a structureless particle is simultaneously exposed to two heat reservoirs, each imposing on one of its motional degrees of freedom. An average gyrating motion can be observed in the nonequilibrium steady state (NESS) [12,13] if the two reservoirs are of distinct temperatures, and hence this two-dimensional Brownian gyrator can serve as a "minimal" version of autonomous heat engines. In Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In particular it was found that the zero mass limit and the over-damping limit are different in reducing the Kramers equation to the FokkerPlanck equation. Kwon, Ao and Thouless [24] studied the diffusion dynamics with a linear drift force in high dimensions and found the probability distribution function (PDF) for the NESS exactly. They found that a circulating probability current can exist at the steady state, violating the detailed balance.…”
Section: Introductionmentioning
confidence: 99%